Die Kaiserin: Reich, Ritual und Dynastie - Keller, Katrin (2021)
Emperors ruled the Holy Roman Empire - didn't they have at least one woman with them? This question is answered for the first time in this book: The empress was not only present when politics was made, but as an agent she was an important player in imperial politics.